Memantine: Reality and Potentiality - Rita Moretti M.D; Paola Torre; Cristina Vilotti; Davide Manganaro; Luca Zanet; Rodolfo M. Antonello (AboutScience Srl, 2008)
Memantine protects cultured neurons from excitotoxin-induced cell-death; it attenuated loss of cholinergic neurons in the CNS induced by injection of NMDA into the basal forebrain of rats. It has been shown that memantine induced production of brain-derived neurotrophic factor (BDNF), a substance shown to promote survival and differentiation of CNS neuron. Due to the preclinical effects of memantine owing to its anti-ischemic and anti-excitotoxic properties, recent clinical efficacy has been demonstrated in patients with advanced dementia of vascular origins. Therefore, it has been employed in different trials, in vascular dementia, showing a potential benefit and no unbearable side effects. Different studies underline the possible role of memantine in Parkinson Disease.